Coolidge Corner, general view, Brookline, Massachusetts, 6 of 7. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Exterior view of a shoping area in Coolidge Corner. Coolidge Corner is a neighborhood of Brookline, Massachusetts, centered around the intersection of Beacon Street and Harvard Street. The neighborhood takes its name from the Coolidge brothers' general store. (Source: Wikipedia) Slide 6 of 7.; Caption on image: Coolidge Corner Brookline, MA.; Binder Number 4. Pocket Number: 7.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.